Embryonic, larval development, growth performance and salinity tolerance of Crassostrea belcheri sowerby and Crassostrea iredalei faustino hybrids - Wan Nawang, Wan Nur Fatin Syafiqah (2016)
Crassostrea belcheri and C. iredalei are two species of tropical oysters found in Malaysian waters. Between these two oysters, C. iredalei is preferred by local consumers due to its tasty and creamy flesh. However, the disadvantage is being small in size. Thus, this study was carried out to hybridize these two oysters, to see whether the resulted hybrids are better in terms of flesh quality, size, growth and survival. Inter-specific hybrids between C. belcheri and C. iredalei were produced in the hatchery of Fisheries Research Institute (FRI), Pulau Sayak, Kedah to assess its potential as an aquaculture species in Malaysia. The specific objectives of these studies were to 1) observe and describe the embryonic and larval development, 2) to evaluate the growth performance, 3) to determine the salinity tolerance of spats, and 4) to determine the protein and fatty acids content of 8 month-old oysters of parental and inter-specific crosses of C. belcheri and C. iredalei. Broodstock of C. belcheri and C. iredalei were collected from Batu Lintang, Kedah. Parental and inter-specific crosses were produced through mechanical stripping. Parental and inter-specific crosses between C. belcheri (CB) and C. iredalei (CI) resulted in crosses of CB♀XCB♂, CI♀XCI♂, CB♀XCI♂ and CI♀XCB♂. Successful fertilization in both inter-specifics crosses confirmed that C. belcheri eggs can be fertilized by C. iredalei sperm and vice versa. The fertilization percentage of interspecific crosses of CB♀XCI♂ (64.77±1.38%) and CI♀XCB♂ (30.23±2.51%) were significantly lower (p<0.05) compared to parental C. belcheri (80.69±1.53%) and C. iredalei (80.05±2.56%). Larviculture were carried out in 300 L tank in triplicates for each crosses. Percentage of survival of all crosses from each larval stages were measured at the end of the study period. However, there were no significant differences in survival (%) of each larval stage in all crosses. Similarly, no significant different (p>0.05) of survival was observed from fertilized eggs to D-stage in inter-specific crosses. Percentage of survival during transition period from D-stage to pediveliger stage in interspecific crosses of CB♀XCI♂ was highest (p<0.05) 25.15±3.67%, followed by parental C. belcheri 16.8±0.38% and C. iredalei 21.02±1.73%, respectively. Pediveliger stage was observed the earliest at 11 days post-fertilization in CI♀XCB♂ while in the other crosses at 13 days post-fertilization. Earliest settlements were observed in CI♀XCB♂ crosses at 12 days post-fertilization, followed by other crosses at 14 days postfertilization. The percentage of fertilization of eggs from CI♀XCB♂ was lowest as compared to other crosses, however faster settlement and metamorphosis were observed. This finding shows that the hybrid progeny has a shorter planktonic stage as compared to progeny from parental crosses. Specific growth rate (SGR) was measured at 3 stages; planktonic (1-13 days), early settlement (13-30 days) and spat (30-100 days) stage. Progeny from CI♀XCB♂ shows highest (p<0.05) SGR and larger in size possibly due to early settlement. At settlement stage, spats from CB♀XCB♂ parental cross showed highest (p<0.05) SGR. Spats of 100 day-old were comparatively larger in inter-specific crosses as compared to spats from CI♀XCI♂. Thus, the progeny from the inter-specific crosses produce comparatively better growth and survival from the planktonic to spat stage. As for salinity tolerance, 3 experiments were conducted. Experiment 1 was conducted to determine the growth and salinity tolerance in 10, 20 and 30 ppt in 40 dayold spats. Experiment 2 was conducted to determine the percentage of spats survival exposed to short term salinity shock in 5, 10, 15, 20, 25, and 30 ppt. In Experiment 3, spats were exposed to three different salinity decrements, gradual, intermediate and rapid. Percentage of survival was determined at the end of experimental period. Spats were able to tolerate the drastic decrement in salinity evidence with 100% survival. Crude protein and fatty acids were measured in 8 month-old oysters. Crude protein was highest (p<0.05) in spats of CB♀CI♂ (56.09±0.64) followed by CI♀CB♂ (57.0±0.56), CB♀CB♂ (53.48±0.42) and then finally CI♀CI♂ (53.94±1.88). This study indicated that spats from inter-specific crosses CB♀CI♂ and CI♀CB♂ higher protein content as compared to parental crosses. Higher polyunsaturated fatty acids were observed in interspecific cross of CI♀XCB♂. These results indicated that the hybrids offers better survival, growth, protein levels and fatty acids composition.